NAP1L5 in acute myeloid leukemia: a prognostic biomarker and potential therapeutic target - Wang, Meng; Xie, Zhibin; Tan, Yuanyuan; Zhou, Yan; Zhang, Tingting; Du, Yuqing; Wu, Huan; Zhou, Lili; Ge, Jian (Frontiers in Oncology, 2025)
BackgroundNucleosome assembly protein 1-like 5 (NAP1L5), a critical regulator of gene transcription and nucleosome assembly, has been implicated in the progression and poor prognosis of various cancers. However, its specific role and molecular mechanisms in acute myeloid leukemia (AML) remain largely unexplored.MethodsTo identify key genes associated with AML, we analyzed gene expression profiles from AML patients and healthy controls using microarray datasets obtained from the GEO database. Differential expression analysis was performed to identify differentially expressed genes (DEGs), among which NAP1L5 emerged as a critical candidate based on its expression patterns and prognostic relevance, and we validated NAP1L5 expression in clinical AML samples. To elucidate the functional role of NAP1L5, we conducted Gene Set Enrichment Analysis (GSEA) and Gene Ontology (GO) analysis, which revealed its involvement in specific signaling pathways and biological processes. Furthermore, we constructed an interaction network and predictive model for NAP1L5, complemented by an assessment of its role in immune infiltration and drug sensitivity. Finally, we conducted in vitro experiments to explore its biological functions and underlying molecular mechanisms.ResultsIn AML, elevated expression of NAP1L5 was significantly associated with reduced overall survival, underscoring its prognostic relevance. GSEA revealed that NAP1L5 was prominently enriched in pathways related to apoptosis and DNA replication. GO analysis further indicated that its co-expressed genes were closely linked to autophagy and stress response mechanisms. Interaction network analysis revealed that NAP1L5 engages in complex regulatory interactions with multiple genes, miRNAs, transcription factors (TFs), and RNA-binding proteins (RBPs). Notably, high NAP1L5 expression correlated with increased infiltration of resting CD4+ memory T cells, implicating its potential influence on the tumor immune microenvironment. A predictive model integrating NAP1L5 expression and clinical AML features exhibited robust prognostic utility. Drug sensitivity analysis identified NAP1L5 overexpression as a marker of resistance to Zibotentan, along with associations with 49 additional therapeutic agents. In vitro functional assays demonstrated that NAP1L5 overexpression promoted cellular proliferation, migration, and colony formation while concurrently inhibiting apoptosis, highlighting its oncogenic potential in AML pathogenesis.ConclusionsNAP1L5 emerges as a promising prognostic biomarker and therapeutic target in AML, offering potential for improved patient outcomes and precision treatment strategies.